Vietnamese information retrieval test collection development - Nguyen, Ba Ngoc (JST: Engineering And Technology For Sustainable Development, 2022)
Linguistic features processing can remarkably affect information retrieval effectiveness. Evaluation is an important phase in the development process of any information retrieval solutions. In the current state, due to the lack of test collections, it’s difficult to carry out research and share achieved results, because of that the development of Vietnamese test collections are required. This report will provide general information about information retrieval evaluation problems, the test collection development and evaluation processes. The achieved results show that information retrieval test collection development can take a lot of time and effort, but can be divided into many phases and can be developed incrementally.